Relationship between Glutathione S-transferase gene deletions (GSTT1 and GSTM1) and coronary artery disease/acute myocardial infarction. - Semra Koc; Davut Alptekin (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: Coronary artery disease (CAD) is the most common disease in heart-related diseases. CAD arises from the contraction of coroner artery, which provides blood for heart tissue. Glutathione S-Transferase (GST) enzymes are known to be associated with CAD. Glutathione S-Transferase M1 (GSTM1) and Glutathione S-Transferase T1 (GSTT1) genes are associated with detoxification or activation of chemicals in cigarette smoke. Mutations in these genes lead decreased enzyme activities and formation of CAD. In this study the relationship between GSTM1 and GSTT1 genes and CAD were investigated in four generations (1-4) of a family with a history of CAD and acute myocardial infarction (AMI). Material and Methods: Patients of a family with known family pedigrees included in the study. The age, use of alcohol, cigarette smoking, and disease history were recorded. Starting from the proband patient the pedigrees from first to fourth generation pedigree were examined. One-hundred venous blood samples obtained from all 4 generation individuals. Glutathione S-Transferase M1 and GSTT1 genes were amplified employing gene specific primers with PCR and visualized by agarose gel electrophoresis. Results: In this family 24 person had CAD and 19 (79%) of them were heavy cigarette smokers. As a result of the molecular analysis, we did not detect any GST polymorphisms. Conclusion: Although several lines of studies indicate an association of CAD with GST gene polymorphisms, in our study no association was found between CAD and GST polymorphisms for all family members tested. Moreover, we did not establish an association between coronary artery diseases and cigarette smoking. [Cukurova Med J 2014; 39(2.000): 256-261]